PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, DAN CAPITAL STRUCTURE TERHADAP KINERJA KEUANGAN DENGAN FIRM SIZE SEBAGAI VARIABEL MODERATING - Nadhifa Arka Athala (2023)
This research is a quantitative study which aims to examine the effect of corporate social responsibility, leverage, capital structure on financial performance with firm size as a moderating variable. The research uses secondary data from the raw goods sector, the energy sector, and the infrastructure sector which are listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Sampling voters using purposive sampling method obtained with a total of 87 samples. Testing the hypothesis in this study uses a multiple linear regression model. The research model was processed and tested using Microsoft Excel 2016 and STATA. The results of this study are: 1) Corporate Social Responsibility has no effect on financial performance. 2) Leverage has no effect on financial performance. 3) Capital Structure has a significant negative effect on financial performance. 4) Company size is not able to moderate the relationship between Corporate Social Responsibility and Financial Performance. 5) Firm size is unable to moderate the relationship between Leverage and Financial Performance. 6) Moderated Capital Structure Company Size has a significant negative effect on Financial Performance.